2017
DOI: 10.24272/j.issn.2095-8137.2017.003
|View full text |Cite
|
Sign up to set email alerts
|

野生动物(野鸟)对全球耐药基因传播的影响

Abstract: Antimicrobial resistance is an urgent global health challenge in human and veterinary medicine. Wild animals are not directly exposed to clinically relevant antibiotics; however, antibacterial resistance in wild animals has been increasingly reported worldwide in parallel to the situation in human and veterinary medicine. This underlies the complexity of bacterial resistance in wild animals and the possible interspecies transmission between humans, domestic animals, the environment, and wildlife. This review s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 152 publications
0
52
2
Order By: Relevance
“…ESBL-producing E. coli in wild animals begun to be documented in 2006, in Portugal (Costa et al, 2006), and then were rapidly observed in other countries from Europe, Africa, Asia, South America, North America and Australia (Allen et al, 2010;Wang et al, 2017).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ESBL-producing E. coli in wild animals begun to be documented in 2006, in Portugal (Costa et al, 2006), and then were rapidly observed in other countries from Europe, Africa, Asia, South America, North America and Australia (Allen et al, 2010;Wang et al, 2017).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…While the exposure to polluted environments constitutes a risk factor for humans to acquire multidrug-resistant (MDR) bacteria, recent studies have pointed out that it could also have implications for wildlife (Cerdà-Cuéllar et al, 2019;Sellera, 2019;Wang et al, 2017). In fact, although this matter remains poorly addressed under ecological perspectives, the scientific community and nature conservation authorities have begun to see wild animals as reservoirs and potential disseminators of ESBL-producing bacteria (Ardiles-Villegas, González-Acuña, Waldenström, Olsen, & Hernández, 2011;Cerdà-Cuéllar et al, 2019;Sellera, 2019;Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The development of bacterial resistance is a naturally occurring evolutionary mechanism of micro-organisms, but the wide spread use and misuse of antibacterial agents in humans and animals has accelerated this process. MCR-1 is one of the few and clear example of the animal origin of a resistance trait that may later hit the entire human health [2,15].…”
Section: Why Wildlife Is So Important To Analyze For Mcr-1 Gene?mentioning
confidence: 99%
“…Wild birds and animals are the potential reservoirs and vectors for the global distribution of MCR-1, it has been identified on Enterobacteriaceae isolates from food-producing animals, companion animal, food products, the environment and humans worldwide [2,19].…”
Section: Global Distribution Of E Coli Harboring Mcr-1 Genementioning
confidence: 99%
See 1 more Smart Citation